1763 Newborn Hearing Screening: The Experience of the University Hospital of Modena. (October 2012) - Palma, S; Roversi, MF; Artioli, FM; Denti, G; Ferrari, F; Genovese, E
Abstract : Background and Aims: Newborn hearing screening programs allow to identify infants with bilateral permanent congenital hearing impairment and to facilitate early intervention to minimize the consequences on language development. In our country the concept of implementing universal newborn hearing screening protocols is still a topic of debate. Our aim was to analyze the first data collected in one year of experience since the adoption of the universal newborn hearing screening in Modena University Hospital. Methods: Data were collected during the period from 8 th April 2011 to 31 st March 2012. The screening was carried out by means of Transient Stimulus Evoked Otoacoustic Emissions, using, for well babies, a two-stage protocol: first screening stage on the second day after birth, followed by re-screening before discharge if a pass response was not obtained from both ears and a second stage follow up screening within 3 weeks later in case of failure. In case of a persistent failure response an audiologic evaluation was performed. Results: During the period of the study 3512 babies underwent newborn hearing screening, of these 203 presented increased risk factors. In well babies group, one child will undergo surgery for a cochlear implant, 3 children are receiving a prosthetic-rehabilitative treatment. The prevalence of permanent bilateral hearing loss resulted 1.2:1000. Conclusion: It is important to create an active collaboration between audiologists/ENT specialists and paediatricians to reach the objective of identifying infants with hearing loss as early as possible in order to implement early interventions.